Clustering of instrumental methods to characterize the texture and the rheology of slimy okra (Abelmoschus esculentus) suspensions. Issue 3 (28th January 2020) - Savouré, Timoty; Dornier, Manuel; Vachoud, Laurent; Collignan, Antoine
Abstract: Okra ( Abelmoschus esculentus ) is one of the ingredients widely used in African gastronomy because of the unique slimy texture it gives to sauces. However, processing and formulation can affect the textural and rheological properties of these sauces, leading to unacceptable quality for the African consumer. The aim of this study was to select the instrumental measurements best enabling (a) characterization of the rheology and texture of slimy sauces prepared from okra and (b) monitoring its evolution during the preservation process. Thirty‐seven slimy suspensions (sauces and purées) were measured with 16 rheological and textural parameters. A principal component analysis revealed that flow consistency index K and flow behavior index n were well correlated with visco‐elastic, adhesive, and shear thinning properties, and that stringiness was well correlated with elongational, cohesive, and ductile properties. These two sets of measurement methods are sufficient to characterize their rheological and textural properties, and necessary to discriminate them according to their process and formulation. Abstract :